Mengoptimalkan Lingkungan Pendidikan: Studi Kasus Manajemen Sarana dan Prasarana - Arfin, Arfin; M., Rahmawati; Bagea, Ishak; Tomi, Tomi (Magister Administrasi Pendidikan, Universitas Muhammadiyah Kendari, 2023)
This study aims to explore and analyze the facility and infrastructure management at SD Negeri 10 Asera, North Konawe Regency, focusing on planning, procurement, inventorying, maintenance, and disposal. The rationale for this research arises from the urgency of effective facility and infrastructure management on the quality of learning, as well as the lack of literature related to such management at the elementary level. The research method used is qualitative with in-depth interviews with nine informants, involving the school principal, vice-principal, and class teachers. The findings indicate that the implementation of facility and infrastructure management at the school involves active participation from the entire school community. The study concludes that these practices contribute positively to the effectiveness of learning and create a conducive environment. This research provides valuable insights into the central role of facility and infrastructure management in advancing the quality of education at the elementary level.